Analisis Peran Penyuluh Agama dalam Meningkatkan Pemahaman Keagamaan Masyarakat di RT 3 Kompi Kota Bengkulu - Anggraini, Anisa; Andayani, Retno; Ramadani, Issabela; Andriansyah, Habi; Muhammad Shaban Rafi (DAWUH : Islamic Communication Journal, 2023)
This research discusses "The Role of Religious Counselors in Improving Religious Understanding for the Community of RT 3 Company Bengkulu City". The purpose of this research is to obtain an objective picture of the role of religious instructors in improving religious understanding for the community. This research uses field research method (field research), which is a method used by conducting research on the object under study by interviewing, observing and documenting. The data source in this research is the religious counselor employees of RT 3 Company Bengkulu City. The data that has been collected from the results of the research was analyzed using descriptive qualitative analysis techniques. The results showed that, 1) The role of religious extension workers (Ustadz) Singaran Pati Subdistrict in increasing religious understanding for the community by educating, straightening, reforming and unifying in providing religious understanding. 2) The method used by religious instructors (Ustadz) RT 3 Company Bengkulu City in increasing religious understanding by conducting direct, individual, group and indirect communication in providing religious understanding for the community. 3) Religious instructors (Ustadz) RT 3 Company Bengkulu City in increasing religious understanding for the community is by providing religious understanding of Akidah, Sharia, and Ahklak.